On the estimation of diesel particulate filter particulate load based on pressure difference - Munthahar, Sayid Achmad (My University, 2024)
Stricter particulate emission regulations have led to the use of Diesel Particulate Filters (DPF), which is one of the exhaust aftertreatment systems utilized to capture engine-out particulates. However, as particulates accumulate within the DPF, the exhaust pressure drop increases which in turn decreases the overall powertrain efficiency. This necessitates an estimation of particulate load for effective regeneration control–a process to oxidize the soot deposits. This thesis evaluates pressure dropbased particulate load estimation by utilizing recursive Least Squares method to estimate the normalized pressure drop. The study reveals the challenges in achieving high accuracy due to the complex nature of the micro-characteristics of the particulates. Moreover, the author explores alternative applications for pressure difference sensors beyond direct particulate load estimation.
Keywords: Heavy-duty vehicle emission; Particulate emission; Diesel Particulate Filter (DPF); Particulate load estimation; Exhaust aftertreatment system